Etnografias visuais e a relação antropólogo/nativo: o caso de Pierre Verger - Gustavo Pereira Campos (2014)
This dissertation aims to explore the anthropologist/native relationship in the development of the anthropological knowledge based on a research taken on by Pierre Verger (1902-1996), and which the results were published in two great works: Dieux dAfrique (1954) and Orixás (1981). Both of them place the photography at the core of the ethnographic narrative, which brings about debates from the field of the visual anthropology. Apart from that, aiming to better understand this relationship, I appropriate ideas and authors that, as I see, show a similar concern to Verger with respect to ethical, esthetical, political, methodological and epistemological issues regarding the anthropological activity.